The Increasing Burden of Cancer Among Women and in Rural Areas: A Retrospective Population-Based Study - Dan Dai MS; Lingfeng Xu MS; Shuowen Fang MS; Zhenqiu Zha PhD; Huadong Wang MS; Zhirong Liu MS; Manman Lu PhD (SAGE Publishing, 2023)
The retrospective study aimed to describe the epidemiological characteristics and trends of cancer in Anhui Province, China between 2010 and 2018. Cancer registry data were analyzed using the Joinpoint regression model to calculate trends in cancer incidence and mortality. Age-standardized incidence rate, calculated based on the world Segi's population (ASIRW) was higher in males (239.34 per 100 000) than in females (157.13 per 100 000), and higher in rural areas (203.98 per 100 000) compared to urban areas (189.93 per 100 000). The ASIRW for males decreased with an AAPC of −3.0%, while that of females showed an upward trend with an AAPC of 2.1%. At the same time, the ASIRW in urban areas decreased with an AAPC of −2.4%, whereas it remained relatively stable in rural areas. Among males, lung cancer was the most prevalent type of cancer, while breast cancer was the most frequent cancer among women. The age-standardized mortality rate according to the world Segi's population (ASMRW) was 115.32 per 100 000. The ASMRW was higher in males (156.70 per 100 000) than in females (75.51 per 100 000), and higher in rural areas (122.18 per 100 000) than urban areas (109.21 per 100 000). Lung cancer accounted for the majority of cancer-associated mortalities in the province. Attention needs to be focused on women and rural areas due to rapidly increasing incidence and mortality rates for cancer. Furthermore, an effective public health response is imperative, encompassing early screening, diagnosis, and treatment of prevalent cancers in high-risk populations and regions. It's crucial to promote healthy lifestyles among the public through health education.